The Impact of Enterprise Risk Management, Strategic Agility, and Quality of Internal Audit Function on Firm Performance - Ping, Teoh Ai; Yeang, Lee Kaih; Muthuveloo, Rajendran (International Review of Management and Marketing, 2017)
This paper examines the relationship of Enterprise Risk Management (ERM) implementation to firm performance, the mediating role of strategic agility and moderating role of quality of internal audit function in this relationship among Malaysian public listed companies (PLCs). ERM implementation was conceptualized with the elements in COSO (2004) ERM Integrated Framework, and firm performance was measured by financial and non-financial indicators. A total of 137 responses were obtained through questionnaire from PLCs in main market of Bursa Malaysia. The empirical findings of the study suggest that ERM implementation has a significant relationship to firm performance and strategic agility significantly mediate the relationship. However, quality of internal audit function does not significantly moderate the relationship between ERM implementation and firm performance. Low response rate presents a challenge to generalize the content to all public listed companies in Malaysia. Due to time and cost constraints this study did not acquire any secondary data and interviews which may provide further in-depth findings related to the research. In this study ERM framework as an integrative risk management has been recognized as the contributor to the firm performance of sample companies. Public listed companies, Securities Commission and Institute of Internal Auditors Malaysia will benefit from the findings of this study. Keywords- Enterprise Risk Management, Strategic Agility, Internal Audit Function, Firm Performance, Malaysia. JEL Classifications: M420, M190